Amiloride Is a Competitive Inhibitor of Coxsackievirus B3 RNA Polymerase - Gazina, Elena V. (American Society for Microbiology, 2011)

(untitled)
Amiloride and its derivative 5-(N-ethyl-N-isopropyl)amiloride (EIPA) were previously shown to inhibit coxsackievirus B3 (CVB3) RNA replication in cell culture, with two amino acid substitutions in the viral RNA-dependent RNA polymerase 3D(pol) conferring partial resistance of CVB3 to these compounds (D. N. Harrison, E. V. Gazina, D. F. Purcell, D. A. Anderson, and S. Petrou, J. Virol. 82:1465–1473, 2008). Here we demonstrate that amiloride and EIPA inhibit the enzymatic activity of CVB3 3D(pol) in vitro, affecting both VPg uridylylation and RNA elongation. Examination of the mechanism of inhibition of 3D(pol) by amiloride showed that the compound acts as a competitive inhibitor, competing with incoming nucleoside triphosphates (NTPs) and Mg(2+). Docking analysis suggested a binding site for amiloride and EIPA in 3D(pol), located in close proximity to one of the Mg(2+) ions and overlapping the nucleotide binding site, thus explaining the observed competition. This is the first report of a molecular mechanism of action of nonnucleoside inhibitors against a picornaviral RNA-dependent RNA polymerase.